Building Ethical Climate in a Foreign Country: A Dilemma for the Foreign Multinationals - Grover, Dimple (International Journal of Social Sciences and Management, 2022)
Ethical climate of an organization gets reflected in the workplace behavior, attitudes and shared perceptions of the members of the organization who are firmly embedded in the national culture. Organizations crossing boundaries to establish their subsidiaries in foreign land are continuously engaged in the balancing act of their own values and principles with that of the business environment of the host country. At the same time, they are competing with the already protected and operating companies of the host country. The purpose of this paper is to enable the organizations to develop an understanding in building Ethical Climate in their organizations in a foreign country. Int. J. Soc. Sc. Manage. Vol. 9, Issue-1: 8-12. Corrections: Conflict of Interest was wrongly placed before conclusion, which was corrected after the conclusion. 2nd Version uploaded on 10-02-2022